Tackling bullying in your school : a practical handbook for teachers - Smith, Peter K.; Sharp, Sonia, 1961- (Routledge Taylor & Francis Group, 1994)
Presents step-by-step advice on developing a whole school policy and suggests methods for tackling bullying through classroom and curriculum activities.